UPAYA UNITED NATIONS OFFICE ON DRUGS AND CRIME (UNODC) DALAM MENANGANI DRUG TRAFFICKING DI AFGHANISTAN PERIODE 2012-2013 - Milatina, Qonita; Hanura, Marten; Windiani, Reni (Journal of International Relations, 2015)
Drug trafficking is an important issue as it can be the source of theemerging of the other crimes. For several years, Afghanistan has leadthe the supply of illegal opiate to the other countries in the world. As apart of United Nations, UNODC has contribute a lot of significantoutputs along with Afghan Government through The CountryProgramme for Afghanistan. However, by 2012-2013, drug traffickingin Afghanistan increased at the highest point compare to the yearsbefore. This research aims to analyse the constraints of UNODC oncombating drug trafficking in Afghanistan, that caused a significantincrease of drug rafficking in Afghanistan. Descriptive-Analysis typeis used in this research to describe the efforts of UNODC, thenanalyse the constraints of UNODC through the implementation ofCountry Programme. The result shows there are some external factorssuch as economic, socio-economic, and political, from Afghanistan,that obstruct the works of UNODC.